Optimisation of automatic generation control performance in two-area power system with pid controllers using mepso / Lu Li - Lu , Li (2018)
Automatic Generation Control (AGC) is used for regulating the electrical power supply in two-area power system and changing the system frequency and tie-line load. The performance of AGC has to be tuned properly so that the performance can be optimized. In this project, modified evolutionary particle swarm optimisation (MEPSO) -time varying acceleration coefficient (TVAC) is proposed for an AGC of two-area power system to optimize its performance by tuning parameters of the PID controllers. Comparison of the performance by using the proposed algorithm and other algorithms was made to identify which algorithm is better in controlling the performance of the AGC. The AGC in two-area power system was constructed and simulated by using MATLAB R2017b software. From the simulation results, it was found that with the same number of PID controllers, the performance of AGC optimised by using MEPSO-TVAC algorithm is better in terms of overshoot and fitness value than using EPSO and PSO algorithms. Also, using MEPSO-TVAC algorithm, the performance of AGC by using two PID controllers is better in terms of rise time and settling time than using one PID controller. Therefore, via implementation of optimisation method, the performance of AGC can be improved by varying the parameters of PID controller.